Continuing Education and the Changing Needs of Rural Communities: A Case Study of Two University Extension Programs at the University Of Saskatchewan, 1911-1964 - Heather Rollwagen; Silvana Romano; Scott McLean (Adult Education Research Conference, 2007)
A historical sociological approach is used to explore the role of University Continuing Education (UCE) in meeting the changing needs of rural communities in Saskatchewan, Canada during the twentieth century. Results yield insight in the relationship between UCE and social change.